Model of teacher work discipline development based on self-awareness in public junior high school - Milatul Rahmawati; Hanif Al Kadri; Rusdinal Rusdinal; Ahmad Sabandi (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2026)
This study aims to develop and evaluate a self-awareness-based coaching model to improve teacher work discipline in junior high schools. A Research and Development (R&D) approach adapted from Borg and Gall was used, involving needs analysis, model design, validation, and field testing. The study was conducted in three public junior high schools in Pasaman Barat Regency, Indonesia, involving 39 teachers and 3 principals. Data were collected through observation, interviews, validation sheets, and questionnaires. The results showed that initial teacher attendance ranged from 88%–90%, below the ≥95% standard, while timely submission of teaching modules ranged from 58%–64%. The developed model achieved a validity score of 4.56 (very valid) and a practicality score of 4.50 (very practical). After implementation, teacher work discipline significantly increased from a pre-test mean of 3.12 (SD = 0.42) to a post-test mean of 4.26 (SD = 0.38), t(38) = 14.82, p < .001, with a large effect size (Cohen’s d = 2.37). Similarly, self-awareness increased from 3.05 (SD = 0.45) to 4.40 (SD = 0.36), t(38) = 16.25, p < .001, with a large effect size (Cohen’s d = 2.60).. In conclusion, the developed model is valid, practical, and effective in improving teacher work discipline through strengthening self-awareness.